(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article is devoted to the methodology of teaching the Russian language, in which the modern methods and methods used in the teaching of the Russian language are analyzed. The article discusses the main difficulties in language learning, students’ problems in deep language acquisition, and what methods can be used to solve these problems. Also, special attention is paid to interactive methods, communicative pedagogy and technologies in the teaching of the Russian language.